Obesity and the risk of Multiple Sclerosis. The role of Leptin - Marrodan, Mariano; Farez, Mauricio F.; Balbuena Aguirre, Maria E.; Correale, Jorge (Annals of clinical and translational neurology, 2021)
Objective To investigate the effects of leptin on different T‐cell populations, in order to gain more insight into the link between leptin and obesity. Methods Three hundred and nine RRMS patients and 322 controls participated in a cross‐sectional survey, to confirm whether excess weight/obesity in adolescence or early adulthood increased the risk of MS. Serum leptin levels were determined by ELISA. MBP83–102, and MOG63–87 peptide‐specific T cells lines were expanded from peripheral blood mononuclear cells. Leptin receptor expression was measured by RT‐PCR and flow cytometry. Bcl‐2, p‐STAT3, pERK1/2, and p27kip1 expression were assayed using ELISA, and apoptosis induction was determined by Annexin V detection. Cytokines were assessed by ELISPOT and ELISA, and regulatory T cells (Tregs) by flow cytometry. Results Logistic regression analysis, showed excess weight at age 15, and obesity at 20 years of age increased MS risk (OR = 2.16, P = 0.01 and OR = 3.9, P = 0.01). Leptin levels correlated with BMI in both groups. The addition of Leptin increased autoreactive T‐cell proliferation, reduced apoptosis induction, and promoted proinflammatory cytokine secretion. Obese patients produced more proinflammatory cytokines compared to overweight/normal/underweight subjects. Inverse correlation was found between leptin levels and circulating Treg cells (r = −0.97, P < 0.0001). Leptin inhibited Treg proliferation. Effects of leptin on CD4+CD25− effector T cells were mediated by increased STAT3 and ERK1/2 phosphorylation, and down modulation of the cell cycle inhibitor P27kip1. In contrast, leptin effects on Tregs resulted from decreased phosphorylation of ERK1/2 and upregulation of p27kip1. Interpretation Leptin promotes autoreactive T‐cell proliferation and proinflammatory cytokine secretion, but inhibits Treg‐cell proliferation.